Management of pulp canal obliterations - Olczak, Katarzyna; Kabacińska, Krystyna; Pawlicka, Halina (Journal of Stomatology, 2017)
Introduction. Pulp canal obliteration may affect all teeth and take various forms. We encounter partial and total pulp canal obliteration as well as obliteration in a form of pulp stones. Aim of study. To present various management approaches and treatment strategies in pulp canal obliteration. Material and method. The study presents clinical cases of different forms of obliteration and treatment options including observation. Results. Endodontic treatment of pulp canal obliteration is challenging and time consuming. Microscope and ultrasonic unit together with different ultrasonic tips are very useful and helpful devices. In some cases observation, rather than endodontic treatment, is recommended without any dental intervention. Conclusions. No compromise with regard to treatment of obliterated teeth has been worked out.